What do German bank customers want? The importance of customer expectations and the failure of the integral customer advisory service - Jessica Hastenteufel; Sabrina Kiszka (Managerial Economics)
Banks and financial service providers are currently facing numerous challenges due to the ongoing cheap money policy of the European Central Bank, an increasingly regulated market environment and a rapidly progressive digitization. The ongoing decline in interest income and the stagnating of a banks commission income are currently leading to a reduction of a banks total income. In addition, there is digitization that brings numerous new competitors into the market and changes the core business models of banks. As a result, the general conditions in the financial sector change fundamentally and continue to do so in the near future. Moreover, the behaviour and expectations of bank customers have changed in a way that factors such as “convenience”, “flexibility” and “speed” have become increasingly important for them. For this reason, we will start with a theoretical overview of the status quo and the current challenges banks are facing and then present the results of our customer survey to highlight the current expectations of bank customers. Based on this, we formulate recommendations for banks on how to meet their customers’ expectations.